Exploring Native Speakerism to Improve EFL Students' English Language Skills - Masruria, Wulida Wahidatul; Annisa, Zahra Kholifia (Universitas Muhammadiyah Magelang, 2026)
English has become the most widely spoken language among speakers of various languages all over the world (Wang & Fang, 2020). Therefore, the annual increase in individuals acquiring English is 12 (Schreiber, 2019). In recent years, native English teachers have been prioritized in English education in Indonesia (Zhang & Solarz, 2022) because of the language authenticity in the classroom. The concept of